A Catalyst for One‐step Isoparaffin Production via Fischer–Tropsch Synthesis: Growth of a H‐Mordenite Shell Encapsulating a Fused Iron Core. Issue 10 (16th July 2013) - Lin, Qihang; Yang, Guohui; Li, Xiaonian; Yoneyama, Yoshiharu; Wan, Huilin; Tsubaki, Noritatsu
Abstract Fused iron (FI), is a general Fischer–Tropsch synthesis (FTS) catalyst and can be used to convert syngas (CO+H2) into normal hydrocarbons. The syntheses of HZSM‐5 or H‐β zeolite‐shell encapsulated catalysts for FTS have been reported previously, however, conventional zeolite‐shell synthesis generally employs an organic template, which is neither economic nor environmentally benign. Here we report the synthesis, without using an organic template, of a millimeter‐sized defect‐free capsule catalyst covered by a MOR zeolite shell (thickness of 23 μm) on FI pellets. The capsule catalyst (HMOR/FI) exhibited excellent performance for FTS, greatly increasing the selectivity of middle isoparaffins. Compared with the pure FI catalyst, the CO conversion of the HMOR/FI capsule catalyst increased remarkably and the iso/n ratio was almost 8 times that of the pure FI catalyst. This report provides an effective route to synthesize a capsule catalyst, which can reduce costs effectively and is also more environmentally benign than the current conventional zeolite‐shell synthesis.